Federal Farmworker Housing Standards and Regulations, Their Promise and Limitations, and Implications for Farmworker Health. (November 2015) - Joyner, Ann Moss; George, Lance; Hall, Mary Lee; Jacobs, Ilene J.; Kissam, ED; Latin, Shelley; Parnell, Allan; Ruiz, Virginia; Shadbeh, Nargess; Tobacman, Janet
The housing available to most farmworkers is substandard and unacceptable in 21st-century America. The federal government established minimal occupational safety and health standards applicable to migrant farmworker labor camps decades ago, and some states have statutory schemes and regulations that set standards for farm labor camps and employee housing. Many of these federal and state regulations no longer reflect current employment and housing trends, and enforcement success varies greatly. These regulations implicitly recognize the connection between housing conditions and health, but do not effectively address that connection. This review describes the current state of farmworker housing, discusses laws and regulations pertaining to such housing, and highlights the literature on health risks associated with inadequate housing. We propose specific recommendations to strengthen enforcement and reduce the risks of substandard housing for the health of farmworkers and their families.